Survival of Xanthomonas campestris pv. campestris in the phyllosphere and rhizosphere of weeds - Silva, J. C. [UNESP]; Silva Júnior, T. A.F.; Soman, J. M. [UNESP]; Tomasini, T. D. [UNESP]; Sartori, M. M.P. [UNESP]; Maringoni, A. C. [UNESP] (Wiley, 2017)
The phyllosphere and rhizosphere of weeds are important niches for phytobacterial survival. The absence of information in Brazil regarding Xanthomonas campestris pv. campestris (Xcc), the causal agent of black rot in crucifers, motivated this study. Twenty-six weed species belonging to 14 botanical families were included in field experiments between August 2014 and October 2015. Lepidium virginicum and Raphanus raphanistrum (Brassicaceae) demonstrated great potential for survival of Xcc in the phyllosphere, with the bacterium isolated after 56 and 70 days, respectively. Low variation between maximum and minimum temperatures, high rainfall and high relative humidity at specific times of the year contributed to longer Xcc survival periods in the phyllosphere of some species. Xcc survived in the rhizosphere only in R. raphanistrum, where it was isolated for up to 28 days. No relation was found between climatic factors and survival in the rhizosphere. The data indicate that control of brassicaceous weeds will contribute to the control of black rot.
Keywords: black rot; brassica; survival; weeds